STRUGGLE AS SEEN IN CASSANDRA CLARE’S THE MORTAL INSTRUMENTS: CITY OF BONES - Muhamad Taufik Ibrahim; Ceysi N Wuntu; Imelda Lolowang (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2021)
This research is entitled Struggle as seen in Cassandra Clare’s The Mortal Instruments: City of Bones. The aim of this study is to find out the struggle in the novel. Objective approach is applied in analysing the data to find out the courage in the novel. Qualitative research is descriptive. The data collected are in form of words and pictures rather than numbers. The objective approach is applied because the analysis only focuses on the novel itself. The results show that there is a lot of struggle. There many struggles that were played by characters in the novel. Through an intrinsic approach, and example in this novel shows attitudes and struggle of the main character named Clary and her mother named Jocelyn they live together in New York. At first, everything was fine, than everything changed when Jocelyn suddenly disappeared. This is where Clary struggles to find her mother, Clary also finds the reason why her mother disappeared. Clary goes through various kinds of obstacles that she has to go through such as fighting against every enemy such as Vampire, Devil, Giant. Clary not only struggles to find her mother, here she also struggles for the one she loves, namely Jace. What make this novel interesting is not only the struggles of the main characters. But there is a moral value in the novel.